Morning Exercise is More Effective in Ameliorating Oxidative Stress in Patients with Type 2 Diabetes Mellitus - Jusup, Sinu; Douwes, Muhsin; Purwanto, Bambang; Indarto, Dono; Hartono, Hartono; Pamungkasari, Eti Poncorini (Open Access Macedonian Journal of Medical Sciences, 2022)
Introduction: Exercise has been believed to be an important step in treating and preventing Type 2 Diabetes Mellitus complications. The circadian rhythm influences systems in the body, including antioxidants in the human body. By synchronizing exercise with exercise time, it will maximize the benefits of exercise for health. Aim: Examining the effect of morning and afternoon exercise on increasing antioxidants and improving oxidative stress in patients with T2DM. Methods: Twenty-two T2DM patients were randomly assigned to morning and afternoon exercise groups. The exercise treatment in this study was in the form of diabetes Persadia gymnastic, for 10 weeks. All participants were taken venous blood before exercise and after the tenth week. The data examined consisted of GPx-1 (Glutathione Peroxidase-1) and MDA (malodialdehyde). The pre and post data were statistically processed using a comparative test. Results: After 10 weeks of exercise, GPx-1 levels increased significantly in both groups (p<0.05). The increase in this enzyme was considerably greater (p<0.05) in the morning group than in the afternoon group (130.37 ± 2.4 h/ml VS 72.38 ± 3.93 h/ml). MDA levels decreased significantly in morning and afternoon groups (p<0.05). The decrease in MDA was significantly greater (p<0.05) in the morning than in the afternoon exercise group (8.22 ± 0.36 nmol/ml VS 5.2 ± 0.86 nmol/ml). Conclusions: Exercise in the morning was more effective in improving oxidative stress by increasing glutathione peroxidase-1 enzyme and reducing malondialdehyde in patients with Type 2 Diabetes Mellitus. Keywords: Exercise; Glutathione Peroxidase; Malondialdehyde, T2DM.